A world of populations transnational perspectives on demography in the twentieth century - Hartmann, Heinrich 1977-; Unger, Corinna R. (Berghahn Books, 2017)
Demographic study and the idea of a "population" was developed and modified over the course of the twentieth century, mirroring the political, social, and cultural situations and aspirations of different societies. This growing field adapted itself to specific policy concerns and was therefore never apolitical, despite the protestations of practitioners that demography was "natural." Demographics were transformed into public policies that shaped family planning, population growth, medical practice, and environmental conservation. While covering a variety of regions and time periods, the essays in this book share an interest in the transnational dynamics of emerging demographic discourses and practices. Together, they present a global picture of the history of demographic knowledge.